2015
DOI: 10.1590/s0100-204x2015000300002
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Piper extracts on Tuta absoluta (Lepidoptera: Gelechiidae) in tomato

Abstract: -The objective of this work was to evaluate the bioactivity of ethanolic leaf extracts from four species of the genus Piper against the tomato leafminer Tuta absoluta (Lepidoptera: Gelechiidae) under laboratory conditions. The evaluated species were: P. amalago var. medium, P. glabratum, P. mikanianum, and P. mollicomum. In the initial screening assay (extract concentration of 2,000 mg L -1 ), all tested extracts caused significant larval mortality, particularly the extract of P. amalago var. medium; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…It was shown that the chemical compounds present in these Piperaceae can be further evaluated among the isolation of active molecules to develop new botanical formulations, especially when we consider that the majority of these substances has been reported as potential insecticides in many other studies conducted worldwide (Santos et al, 2010;2013;Cáceres & Kato, 2014, Brito, Baldin, Silva, Ribeiro, & Vendramim, 2015Krinski & Foerster, 2016, Sanini et al 2017, Turchen, Hunhoff, Paulo,Souza, Pereira, 2016b and other plant families (Isman, 2000;Koul, Walia, & Dhaliwal, 2008;Tripathi, Upadhyay, Bhuiyan, & Bhattacharya, 2009;Coitinho, Oliveira, Gondim-Júnior, & Câmara, 2010;Ntalli & Menkissoglu-Spiroudi, 2011, Zoubiri & Baaliouamer, 2011Baskar, Muthu, Raj, Kingsley, & Ignacimuthu, 2012;Krishnappa & Elumalai, 2012;Cáceres & Kato, 2014Krinski, Massaroli, & Machado, 2014;Backiyaraj et al, 2015;Massaroli, Pereira, & Foerster;Costa, Santana, Oliveira, & Serrão, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the chemical compounds present in these Piperaceae can be further evaluated among the isolation of active molecules to develop new botanical formulations, especially when we consider that the majority of these substances has been reported as potential insecticides in many other studies conducted worldwide (Santos et al, 2010;2013;Cáceres & Kato, 2014, Brito, Baldin, Silva, Ribeiro, & Vendramim, 2015Krinski & Foerster, 2016, Sanini et al 2017, Turchen, Hunhoff, Paulo,Souza, Pereira, 2016b and other plant families (Isman, 2000;Koul, Walia, & Dhaliwal, 2008;Tripathi, Upadhyay, Bhuiyan, & Bhattacharya, 2009;Coitinho, Oliveira, Gondim-Júnior, & Câmara, 2010;Ntalli & Menkissoglu-Spiroudi, 2011, Zoubiri & Baaliouamer, 2011Baskar, Muthu, Raj, Kingsley, & Ignacimuthu, 2012;Krishnappa & Elumalai, 2012;Cáceres & Kato, 2014Krinski, Massaroli, & Machado, 2014;Backiyaraj et al, 2015;Massaroli, Pereira, & Foerster;Costa, Santana, Oliveira, & Serrão, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanolic leaf extract obtained from Piper amalago var. medium, for instance, caused 70% larval and pupal mortality in twoAynalem 15 day exposure through exhibiting acute toxicity at the concentration of 2,000 mg L -1 (de Brito et al, 2015). The allelochemicals found in Piperaceae are diverse with insecticidal/insectistatic properties (Scott et al, 2008).…”
Section: Biochemical Bio-pesticides (Plant Extracts)mentioning
confidence: 99%
“…Essentiële olie uit groene kardemom (Elettaria cardamomum) uit de gemberfamilie heeft een insecticide effect op de eitjes, het 2 de larvale stadium van de rupsen in en op het blad en de motjes van T. absoluta met respectievelijk LC50 waarden van 351.19, 7.88, 1.55 en 1.88 μl/ml lucht (Chegini and Abbasipour 2017). Meerdere publicaties geven aan dat hoge afdoding tot 100% van verschillende stadia mogelijk is (Adil et al 2015b) (Brito et al 2015) (Abdel-Baky and Al-Soqeer 2017) (Ebadah et al 2016). Effectiviteit is vooral getest op eitjes, rupsen en adults, onderzoek naar poppen is beperkt.…”
Section: 343unclassified